Os crevo-mozog: význam interakcií medzi crevnou mikrobiotou a mozgom za fyziologických a patologických situácii - Tomova, A; Pivovarciová, A; Babinská, K; Mravec, B (Ceskoslovenska fysiologie, 2015)
Commensal bacteria of the digestive tract are separated from the brain by multiple barriers. Despite that bacteria residing in the intestine and the neurons of the brain interact by neural and humoral pathways. Mental processes, such as the stress response, may affect the composition and function of intestinal bacteria via the brain-gut axis. On the other hand, intestinal bacteria can influence the processes in the brain through the gut-brain axis. Disruption of these interactions may be involved in various alterations both in the function of the gastrointestinal tract and the brain function.
Keywords: střevní mikroflóra; mozek; Gastrointestinal Microbiome; lidé; deprese; Depression; Humans; Mental Disorders; duševní poruchy; Brain